Mechanisms of controlled crystallization of struvite-K by NTA and EDTA sodium salts - Viani, Alberto; Zarybnicka, Lucie; Sevcik, Radek; Macova, Petra; Machotová, Jana (Elsevier Science BV, 2023)
The mechanisms by which ethylenediaminetetraacetic acid (EDTA) and nitrilotriacetic acid (NTA) sodium salts control the precipitation of struvite-K from solution have been investigated at room temperature, pH = 9, two degrees of supersaturation and two stirring speeds. The interest spans from the potassium and phosphorus recovery from wastewaters, the prevention of scale deposits in wastewater treatment plants, to the modification of magnesium phosphate cement reaction. Both molecules influenced the spontaneous precipitation by extending the induction time, reducing the apparent rate of crystallization and the amount of reaction product. When adding 20 mM of EDTA, at the highest supersaturation degree, the rates dropped from 2.14 min-1 and 4.09 min-1 to 1.36 min-1 and 1.71 min-1, under fast and slow stirring speed conditions, respectively. Conversely, at lower supersaturation the precipitation was almost completely inhibited. Similar inhibiting effect was observed for NTA. The additives were found to influence the reaction path by exploiting their complexing ability in solution, thus depressing the supersaturation degree in Mg2+ ions with respect to struvite-K, and by molecular adsorption at the forming solid surfaces, hindering nucleation and crystal growth. The surface adsorption process has been confirmed by the more negative zeta potential measured on the crystals (from-14.5 +/- 1.0 mV to-17.0 +/- 1.6 mV and-20.8 +/- 3.0 mV for EDTA and NTA, respectively). Both additives induced an overall reduction in crystal size (up to 85 %) and a reduced elongation of the precipitated crystals (aspect ratio decreasing from 2.3 to 1.3 and 1.7 for EDTA and NTA, respectively) in consequence of the preferential adsorption at the (101) and (1 01) faces.
Mechanismus řízené krystalizace struvitu-K pomocí NTA a sodné soli EDTA
Keywords: Adsorption; Nucleation; Phosphates; Minerals; Adsorpce; Nukleace; Fosfáty; Minerály